Investigation of the Laser Material Interaction of Lithium Copper Foils Under Different Process Gases for All-Solid-State Batteries - Lars O. Schmidt; Houssin Wehbe; Sven Hartwig; Maja W. Kandula (Batteries)
Lithium metal exhibits strong adhesive properties and a highly reactive nature, which complicates conventional mechanical separation methods. Laser cutting, as a contactless process, is possible under a defined drying room atmosphere. However, it is a costly process and therefore not suitable for industrial usage. Consequently, the development of a cost-effective process gas is imperative for the future implementation of lithium metal. In this research, the laser cutting of 30 µm lithium copper composite foil is performed under different process gases (nitrogen and argon) and ambient atmospheres with different water contents to determine the ablation potential depended on the process gas. To assess the laser–material interaction, the impact of pulse repetition frequency and cutting velocity on the material behavior was investigated. To this end, the ablation behavior, the resulting cutting edges, and the electrochemical performance were thoroughly explored. The findings reveal a dependence of the ablation behavior on the water content in the ambient atmosphere, as well as a reduced energy input for a complete shot through when using an inert gas. The resulting cutting edges result in nearly similar outcomes with regard to the heat-affected zone. The electrochemical performance illustrates the influence of the laser process with different gases, taking into account the changed electrochemical impedance spectroscopy.